The Effect of Musyarakah Contracts on Profitability at KSPPS BMT Mentari Bumi - Oktafianus Yoga Tri Kusnandar; Isman (al-Afkar, Journal For Islamic Studies, 2023)
To determine how musyarakah contracts affect the profitability (ROA and ROE) of KSPPS BMT Green Earth financial institutions, this study employs a quantitative method that correlates with secondary data extracted from their financial statements for the years 2020-2022. The analysis includes descriptive statistical tests, linear regression, correlation, and hypothesis testing. The results indicate that the musyarakah contract has a strong correlation with and can boost profitability. To demonstrate the importance of musyarakah contracts to a company's profitability, they have a significant impact on ROE, but not on ROA. This study is limited by its reliance on homogeneous sample data and its exclusive focus on the relationship between two profitability measures. In order to obtain a deeper understanding, future research should examine a more diverse sample and include additional variables.